2016
DOI: 10.1007/s12663-016-0943-1
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Invasion of Oral Squamous Cell Carcinoma: A New Hurdle for Surgeons

Abstract: The high rate of mortality associated with cancer is due to its inherent nature to metastasize. Perineural invasion (PNI) is a relatively rare mode of metastasis, and a distinct pathologic entity that can be observed in the absence of lymphatic or vascular invasion which is still shrouded by mystery. PNI is a marker of poor prognosis. Despite increasing recognition of this metastatic process, there has been little progress in the understanding of mechanisms behind PNI. The purpose of this article is to make su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Studies have found that some cancer genes and tumor suppressor genes may be crucial in enhancing or initiating the development of OSCC. Nevertheless, the specific molecular pathways underlying the development of OSCC are still unclear [6][7][8]. Therefore, it is important to elucidate the genomic and epigenomic mechanisms participating in multistep carcinogenesis and the progression of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that some cancer genes and tumor suppressor genes may be crucial in enhancing or initiating the development of OSCC. Nevertheless, the specific molecular pathways underlying the development of OSCC are still unclear [6][7][8]. Therefore, it is important to elucidate the genomic and epigenomic mechanisms participating in multistep carcinogenesis and the progression of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…PNI was initially thought to spread via perineurium or epineurium of the nerve sheath but this theory was later discarded as the ultra-scans of nerve sheath showed it as a highly selective barrier. Latest studies demonstrate that PNI occurs through various molecular interactions between tumor cells and nerve [6].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, both modalities allow detection of advanced perineural spread, a factor potentially influencing the extent of surgery as well as of adjuvant radiotherapy. [22][23][24][25][26] 26 Hirshoren et al 26 evaluated the role of PET/CT in surgical candidates with node-positive cSCCHN. Although not all included patients underwent both parotidectomy and neck dissection, the authors showed that the addition of PET to standard CT changed surgical planning only in 6.25% of patients.…”
Section: Discussionmentioning
confidence: 99%